The New Recreational Transportation on the Street: Personal Mobility, Is It Safe? - Young Woo Kim; Won Bin Park; Jin Seong Cho; Sung Youl Hyun; Geun Lee (Journal of Trauma and Injury)
Purpose The interest in the personal mobility started to grow and as the interest increases, there are growing concerns about the safety of it. The purpose of the study is to look at the types and dynamics of patients injured by the personal mobilities. Methods This was a retrospective 2-year observational study, from January 2016 to December 2017, on the patients who visited the emergency center and the trauma center, with an injury related to driving the personal mobility. Cases of the personal mobility-related accident were collected based on electronic medical records and hospital emergency department-based injury in-depth surveillance data. Results A total of 65 patients visited the emergency center and the trauma center, during this study period. Six patients of 50 adults admitted the alcohol consumption (12%) and two adult patients wore the helmet as the protection gear (3.1%). The number of the patients in 2017 rises three times more than the number of patients in 2016 (51 vs. 14). Injuries to the head and neck region (67.7%) was the most common, followed by the upper extremity (46.2%). Eleven patients (16.9%) were admitted to the hospital, of whom three were admitted to the intensive care unit due to intracranial hemorrhage. Nine patients underwent surgery. Conclusions The use of the personal mobility will continue to grow and the accidents, caused by the vehicle, will increase along with it. The study showed the damage is worse than expected. Personal mobility currently has a limited safety laws and the riders are not yet fully aware of its danger. The improvement of the regulation of the personal mobility, safety education is needed.